Tinjauan Yuridis Terhadap Sidang Praperadilan Berdasarkan Undang-Undang Nomor 8 Tahun 1981 Tentang Hukum Acara Pidana - Abraham Desaloka S; Mexsasai Indra; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Talking about criminal law often makes people imagine everything that is evil, dirtyand full of deception. When people talk about criminal law, what comes to mind is theeradication of crime by the police, prosecutors and judges. The criminal justice system isdiscussed in the criminal justice procedural law regulated in Law Number 8 of 1981. However,in legal practice the suspect's right to take legal action in the pretrial process may not begranted by the legal authorities on the grounds that the main case has been transferred to court. And the unprofessionalism of law enforcers makes it difficult for pretrial hearings to realizepretrial as an effort to defend the rights of a suspect. The impact of the weaknesses in theexisting rules in the pretrial court case process has resulted in futile law enforcement by legalsubjects in defending their rights. So that new regulations are needed that can guarantee thatthe pretrial hearing process can run so that suspects get legal certainty.This research uses the type of normative juridical research, namely research that isfocused on examining the application of the rules or norms in law to legal principles. The datacollection technique used in this study was a literature study. The approach used in this studywas to use a normative approach, namely library law research.The results of the research conducted by the author are first, making rules regardingthe pretrial case delegation process can be said to be important, this is because in pretrialhearings there are many violations committed by law enforcers such as delaying attendance ofpretrial hearings, then rushing cases principal to court with the aim of aborting the ongoingpretrial. Second, in the process of determining suspects carried out by law enforcement, therewere many violations that were not in accordance with the criminal procedure law and alsomany violations of the code of ethics of the law enforcers themselves.Keywords; Pretrial-Criminal Procedural Law